Electrochemical restructuring of thin layer indium tin oxide electrode arrays for optimized (bio)electrocatalysis. (1st January 2018) - Frank, Ronny; Klenner, Marcus; Zitzmann, Franziska D.; Schmidt, Sabine; Ruf, Thomas; Jahnke, Heinz-Georg; Denecke, Reinhard; Robitzki, Andrea A.
Abstract: Bioelectrochemical research has elicited the potential of indium tin oxide (ITO) as a transparent electrode material for biological applications such as enzyme or cell coupled electrodes, especially in the context of integrated devices (multi-electrode arrays and lab-on-chip systems). Due to the miniaturized and multi-material nature of these devices, high sensitivity, cleaning and reuse tend to be difficult and are thus of pivotal interest. In this regard, our goal was to explore an electrochemical surface restructuring process based on a cyclic cathodic polarization in hydrochloric acid (E-HCl), to prepare ITO for electrochemical and bioelectrocatalytic purposes. As studied by AFM, E-HCl shapes a columnar-like surface morphology by etching, thereby producing a fresh surface with an enlarged surface area. Contact angle measurements showed an increased wettability. XPS analysis of the O 1s signal implied a higher fraction of oxygen vacancy sites which are commonly linked to a higher conductivity, while the Sn/In ratio is not affected by the treatment. The restructuring process improved the interfacial electron-transfer of the ferri-/ferrocyanide and FAD/FADH2 redox couple by at least the factor of two as measured by cyclic voltammetry and electrochemical impedance spectroscopy. Moreover, we demonstrate the applicability of the treatment and the sum of its effects on the bioelectrocatalysis of immobilized flavocytochrome P450 BM3. As measured by direct product quantification, the activity was increased more than twofold compared with the HCl control, clearly surpassing the effect which would be due to an increase in the surface area alone. Overall, the combination of an improved interfacial electron-transfer, an increased surface area and the indication of a higher surface polarity and wettability make E-HCl restructuring suitable not only for ITO electrode cleaning and regeneration, but also for surface preparation and post-processing of bioelectrocatalytic electrodes within multi-electrode environments. Graphical abstract: